MODERASI KERUKUNAN UMAT BERAGAMA DALAM MEWUJUDKAN HARMONI KERUKUNAN BERAGAMA DI INDONESIA PADA SERIAL KONTEN LOG IN PADA CHANNEL YOUTUBE DEDDY COUBUZIER - Hidayatullah, Mahdi; Husna, Kania; Mahfuzah, Ghina Sofia (Studia Sosia Religia, 2023)
This research discusses the moderation of religious harmony in realizing religious harmony in Indonesia in the log in content series on Deddy Coubuzier's youtube channel. The main purpose of this research is to find out how religious harmony. This research method involves a qualitative analysis of content analysis of the religious harmony moderation material held by Deddy Coubuzier in the log in content series, including the content, approach, and views conveyed. The results show that with the moderate attitude promoted by the Indonesian people, all differences in religion will not be an obstacle to prioritizing brotherhood in humanity. The presence of the login content series hosted by Habib Ja'far and Onad is a refreshing sight that the beauty of human life in religious differences. Therefore, the role of various parties is needed, especially the government, religious leaders and community activists to continue to provide an understanding of the importance of respecting religious differences.